Changes in the physical properties and specific mechanical energy of corn-mango peel extrudates - Mohamad Mazlan, Mazween; A. Talib, Rosnita; Taip, Farah Saleena; Chin, Nyuk Ling; Sulaiman, Rabiha; Shukri, Radhiah; Mohd Nor, Mohd Zuhair (Taylor and Francis, 2020)
A corn-mango peel blend was processed using a laboratory-scale single-screw extruder, which led to the determination of the apparent density, yellowness, and specific mechanical energy of the extrudate. The effects of the extrusion variables (barrel temperature from 75–175°C, screw speed from 76–100 rpm, feed moisture from 15–21%, and mango peel powder addition from 0–33.33%) were analyzed, and predictive models were obtained using the response surface methodology (RSM). At elevated barrel temperature and screw speed, the extrudates’ apparent density decreased but then increased when the feed moisture and mango peel powder addition increased. At increasing barrel temperature but decreasing mango peel powder addition, the yellowness intensity decreased, and the same response was observed at a low barrel temperature and high mango peel powder addition. The calculated specific mechanical energy (SME) for the production of corn-mango peel extrudate was decreased as the barrel temperature increased.